Rare earth elements (REE) in wild macrofungi: a review highlighting the importance of requisite analytical methodology on data quality - Jerzy Falandysz; Alwyn R. Fernandes; Anna Kilanowicz; Heesoo Eun (Roczniki Panstwowego Zakladu Higieny)
The accelerating global use of lanthanides in modern consumer goods has introduced a new source of environmental pollution and potential health hazards. Evaluating risk for human exposure to these rare earth elements (REE) is hampered by limited occurrence data in foods, partly because reliable, sensitive and accurate determination is challenging. An objective of this work was to critically review lanthanide occurrence in fruiting bodies (mushrooms) of edible wild terrestrial (epigeic) and subterranean (hypogeic) macrofungi and their soil substrates, while also assessing the reported data for analytical quality. Given the paucity of information, all available literature on lanthanides in wild mushrooms was considered. Key requirements for credible REE determination in fungal biomass include avoiding cross contamination from substrates, exclusion of spectral/non-spectral interferences through robust purification and selective, sensitive measurement procedures, inclusion of the full range of lanthanides and strict quality control. In general, both high and lower resolution ICP-MS techniques were evidentially able to provide more reliable outcomes if these requirements were followed. A second objective was to propose a rational approach to assess data reliability by combining the above methodological attributes with the characteristics of lanthanide occurrence in mushrooms: (i) adherence to Oddo-Harkins order, visualised as a descending sawtooth pattern – a result of unfractionated uptake and accumulation of lanthanides from soils and other substrates (ii) typical individual concentration ratios (e.g., La/Sm, Ce/Nd, Ce/Sm) that indicate reliable determination, (iii) bio-exclusion of lanthanides by wild fungi (bioconcentration factors < 1). Data from studies that met these requirements confirmed typically low concentrations (0.07 μg kg-1 of Lu in Suillus luteus to 940 μg kg-1 of Ce in Cantharellus minor ) with patterns corresponding to Oddo-Harkins order across reported fungal types, maintaining the unfractionated REE substrate patterns. However, given the upward trend in REE usage, the continued monitoring of macrofungi is prudent.